Corrigendum to “The impact of experimental variables in twitch tension recording on triphasic action of phospholipase A2 neurotoxins at the neuromuscular junction and acetylcholine release” [Toxicon 266 (2025) 108512] - Behrooz Fathi Hafshejani; Alan L. Harvey; Edward G. Rowan; Azam Mohammadi (Toxicon, 2026)

The impact of experimental variables in twitch tension recording on triphasic action of phospholipase A2 neurotoxins at the neuromuscular junction and acetylcholine release - Behrooz Fathi Hafshejani; Alan L. Harvey; Edward G. Rowan; Azam Mohammadi (Toxicon, 2025)

Informatics for toxicokinetics - Gilberto Padilla Mercado; Christopher Cook; Norman Adkins; Lucas Albrecht; Grace Cary; Brenda Edwards; Derik E. Haggard; Nancy M. Hanley; Michael F. Hughes; Anna Jarnagin; Tirumala D. Kodavanti; Evgenia Korol-Bexell; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

A sea of birds: first bird population assessments in the Saudi Arabian Red Sea - Licia Calabrese; Julie Ann Riordan; Imogen Anne Lloyd; Alexa Darby Foster; Thomas Edward Collier; Johannes Alexandre Chambon; Yasir Wusayl Aljohani; Essa Ali Alhamdi; Patrick Rowan Beaumont; Ivor Douglas Williams; Omar Al-Attas (Frontiers in Marine Science, 2024)
Introduction Seabirds and other insular birds are an important part of marine ecosystems and are increasingly threatened worldwide. Phenology, abundance, distribution, and breeding success are important baseline parameters needed to evaluate population trends and dynamics, identify biodiversity hotspots and potential breeding sites, and assess habitat selection. In the Red Sea basin, reliable and complete data on birds are lacking for islands in most of the Important Bird Areas (IBA). Such data are now especially important since development projects have started at several of these locations. Here, we assess the distribution, abundance, phenology, and population trends of 13 bird species that breed in the Duba Islands, Al Wajh Bank, and Al Lith Islands. Breeding success and habitat selection for six species were also assessed. Methods Between December 2020 and August 2023, more than 90 islands were visited multiple times with different frequencies. All nests were counted, and the area occupied by the different colonies was georeferenced. Breeding success was assessed by visiting selected colonies multiple times until the chicks were ready to fledge. Habitat selection was determined by analyzing the habitat found in the georeferenced colonies. Results More than 25,000 nests were counted each year, mainly in the summer, on more than 75 islands. Of the 13 species studied, the most abundant and widespread species was the White-cheeked tern, and the second most widespread was the Osprey. Discussion We estimate that the Al Wajh Bank hosts the following percentages of global breeding populations: Crab plover: 5%, Sooty gull: 17%–35%, White-eyed gull: 15%, Bridled tern: 1%, White-cheeked tern: 4%, and Lesser crested tern: 2%, making the area a regional and global hotspot for these species. Some of the islands occupied by breeding birds are slated for development for tourism activities as part of the Kingdom’s tourism expansion plans. At the same time, there are several ambitious conservation programs underway in these areas. To be effective, such programs require reliable and comprehensive data of the kind presented here.

Climate driven shifts in the synchrony of apple (Malus x domestica Borkh.) flowering and pollinating bee flight phenology - Chris Wyver; Simon G. Potts; Rowan Edwards; Mike Edwards; Deepa Senapathi (Agricultural and Forest Meteorology, 2023)

Elevated CO 2 does not alter behavioural lateralization in free‐swimming juvenile European sea bass ( Dicentrarchus labrax ) tested in groups - Dominic M. Jarvis; Edward C. Pope; Mathieu Duteil; Ines Fürtbauer; M. Rowan Brown; Richard J. Davis; Andrew J. King (Journal of Fish Biology, 2022)
The authors investigated left–right turning preferences of n = 260 juvenile European sea bass ( Dicentrarchus labrax ) reared in ambient conditions and ocean acidification (OA) conditions or in ambient conditions but tested in OA water. Groups of 10 individuals were observed alone in a circular tank, and individuals' left and right turning during free‐swimming was quantified using trajectory data from the video. The authors showed that near‐future OA levels do not affect the number of turns made, or behavioural lateralization (turning preference), in juvenile D. labrax tested in groups.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Recent advances in therapeutic applications of neutralizing antibodies for virus infections: an overview - Manasik Gumah Ali; Zhening Zhang; Qi Gao; Mingzhu Pan; Edward G Rowan; Juan Zhang (Immunologic Research, 2020)

Neurotoxicity of Tityus bahiensis (brown scorpion) venom in sympathetic vas deferens preparations and neuronal cells - Rita de Cássia Collaço; Stephen Hyslop; Thalita Rocha; Valquiria A. C. Dorce; Edward G. Rowan; Edson Antunes (Archives of Toxicology, 2020)
Systemic scorpion envenomation is characterized by massive neurotransmitter release from peripheral nerves mediated primarily by scorpion venoms neurotoxins. Tityus bahiensis is one of the medically most important species in Brazil, but its venom pharmacology, especially regarding to peripheral nervous system, is poorly understood. Here, we evaluated the T. bahiensis venom activity on autonomic (sympathetic) neurotransmission by using a variety of approaches, including vas deferens twitch-tension recordings, electrophysiological measurements (resting membrane potentials, spontaneous excitatory junctional potentials and whole-cell patch-clamp), calcium imaging and histomorphological analysis. Low concentrations of venom (≤ 3 μg/mL) facilitated the electrically stimulated vas deferens contractions without affecting postsynaptic receptors or damaging the smooth muscle cells. Transient TTX-sensitive sustained contractions and resting membrane depolarization were mediated mainly by massive spontaneous ATP release. High venom concentrations (≥ 10 μg/mL) blocked the muscle contractions and induced membrane depolarization. In neuronal cells (ND7-23 wt ), the venom increased the peak sodium current, modified the current-voltage relationship by left-shifting the Na v -channel activation curve, thereby facilitating the opening of these channels. The venom also caused a time-dependent increase in neuronal calcium influx. These results indicate that the sympathetic hyperstimulation observed in systemic envenomation is presynaptically driven, probably through the interaction of α- and β-toxins with neuronal sodium channels.

Neurotoxicity of Micrurus lemniscatus lemniscatus (South American coralsnake) venom in vertebrate neuromuscular preparations in vitro and neutralization by antivenom - Rafael S. Floriano; Raphael Schezaro-Ramos; Nelson J. Silva; Fábio Bucaretchi; Edward G. Rowan; Stephen Hyslop (Archives of Toxicology, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Characterisation of the antiproliferative constituents and activity of Ficus exasperata (Vahl) on ovarian cancer cells –a preliminary investigation - Enitome E. Bafor; Jennifer McKenna; Edward G. Rowan; RuAngelie Edrada-Ebel (Natural Product Research, 2017)

Whole‐genome resequencing uncovers molecular signatures of natural and sexual selection in wild bighorn sheep - Marty Kardos; Gordon Luikart; Rowan Bunch; Sarah Dewey; William Edwards; Sean McWilliam; John Stephenson; Fred W. Allendorf; John T. Hogg; James Kijas (Molecular Ecology, 2015)
The identification of genes influencing fitness is central to our understanding of the genetic basis of adaptation and how it shapes phenotypic variation in wild populations. Here, we used whole‐genome resequencing of wild Rocky Mountain bighorn sheep ( Ovis canadensis ) to >50‐fold coverage to identify 2.8 million single nucleotide polymorphisms ( SNP s) and genomic regions bearing signatures of directional selection (i.e. selective sweeps). A comparison of SNP diversity between the X chromosome and the autosomes indicated that bighorn males had a dramatically reduced long‐term effective population size compared to females. This probably reflects a long history of intense sexual selection mediated by male–male competition for mates. Selective sweep scans based on heterozygosity and nucleotide diversity revealed evidence for a selective sweep shared across multiple populations at RXFP 2 , a gene that strongly affects horn size in domestic ungulates. The massive horns carried by bighorn rams appear to have evolved in part via strong positive selection at RXFP 2 . We identified evidence for selection within individual populations at genes affecting early body growth and cellular response to hypoxia; however, these must be interpreted more cautiously as genetic drift is strong within local populations and may have caused false positives. These results represent a rare example of strong genomic signatures of selection identified at genes with known function in wild populations of a nonmodel species. Our results also showcase the value of reference genome assemblies from agricultural or model species for studies of the genomic basis of adaptation in closely related wild taxa.

Beak and feather disease viruses circulating in Cape parrots (Poicepahlus robustus) in South Africa - Guy L. Regnard; Rutledge S. Boyes; Rowan O. Martin; Inga I. Hitzeroth; Edward P. Rybicki (Archives of Virology, 2015)

Beak and feather disease virus: correlation between viral load and clinical signs in wild Cape parrots (Poicepahlus robustus) in South Africa - Guy L. Regnard; Rutledge S. Boyes; Rowan O. Martin; Inga I. Hitzeroth; Edward P. Rybicki (Archives of Virology, 2015)